Role of Human Resource Management on Employee’s Well-Being: A Case Study of Central Library, Mizoram University: Examining the impact of Human Resource Management on employee well-being in Mizoram University's Central Library (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The purpose of this study is to look into the function of human resource management in the well-being of Mizoram University’s central library employees. Employee well-being issues at work, such as recruiting, remuneration, work distribution, training, development, and security, were explored in the study. Well-structured questionnaires were distributed to library staff for the study, and they all returned them. The study’s findings demonstrate that library employees' well-being must be prioritized, with changes and improvements made as needed, because a satisfied employee produces higher productivity.